Lost : The Mystery of Amelia Earhart - Bourke, Kenna (NewYork Cambridge University, 2014)
In 1937, pilot Amelia Earhart set out to fly around the world. She never returned. Can this timeless mystery be solved?
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: English language; Elementary level